A spraying material based on perovskite stress luminescence, preparation method and application thereof

By using a new spray material based on perovskite stress luminescence in coal mine tunnels, the problems of tunnel surrounding rock support and stress and strain detection are solved, the high toughness and real-time dynamic luminescence function of the material are realized, and the monitoring process is simplified.

CN118754579BActive Publication Date: 2025-03-07CCTEG COAL MINING RES INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410940179.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2025-03-07
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

After the excavation of coal mine tunnels, the spraying material has poor toughness, which is easy to be damaged after being pressed by the tunnel, and loses the supporting sealing effect. At the same time, the tunnel stress and strain detection methods are complex, and the workload is large, making it difficult to monitor dynamically in real time.

Method used

A spray material based on perovskite stress luminescence was developed. By adding poor solvents to the good solvent of the perovskite precursor and ultrasonic treatment, perovskite nanocrystals with stress luminescence effect were prepared, combining nano-reinforced particles and nano-toughened fibers to enhance the toughness and luminescence properties of the material.

Benefits of technology

The high toughness and stress luminescence function of the sprayed material is realized, and it can emit light dynamically in real time under the deformation stress of the coal mine tunnel. It collects light signals through the visual camera, reflects the stress and deformation of the tunnel in real time, simplifying the detection process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118754579B_ABST
    Figure CN118754579B_ABST
Patent Text Reader

Abstract

The present application embodiment proposes a shotcrete material, preparation method and application based on perovskite stress luminescence, wherein a poor solvent is added to a good solvent of a perovskite precursor, and the pH of the mixed solution is adjusted after ultrasonic treatment, and the mixed solution is stirred, filtered and dried to prepare perovskite nanocrystals with stress luminescence effect; wherein the addition ratio of the good solvent to the poor solvent is 3:1; by mass, 15-25 parts of perovskite nanocrystals, 5-15 parts of nano-enhanced particles, 3-8 parts of nano-toughened fibers and 3.5 parts of additives are added to 100 parts of gelling material, and the dry powder is stirred to obtain the shotcrete material. The shotcrete material in this application can warn of deformation of coal mine lanes, emit light under the action of deformation stress of coal mine lanes, and collect the intensity and distribution of light signals emitted by lane stress in real time and dynamically through a visual camera during the application process, and reflect the ground stress and deformation of the coal mine lanes in real time and dynamically.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of mining engineering technology, and in particular to a spraying material based on perovskite stress luminescence, a preparation method and an application thereof. Background Art

[0002] After the excavation of coal mine tunnels, the support method of shotcrete is generally adopted, which can improve the stress state of the tunnel surrounding rock and solve the problems of tunnel surrounding rock weathering and metal mesh component corrosion failure. However, the surrounding rock of soft rock tunnels usually has a large deformation, and shotcrete is a brittle material with poor toughness. It is easy to be stretched and damaged after the tunnel is pressed, and the supporting and sealing effect on the surrounding rock is lost. At the same time, the detection of tunnel stress and strain requires drilling, installation of stress and strain monitoring equipment, data acquisition signal connection and calibration monitoring. The traditional detection method has complex procedures and large workload. At present, the poor toughness of the shotcrete layer in the coal tunnel and the difficulty in detecting the stress and strain of the tunnel have become a problem restricting the control and detection of the tunnel surrounding rock. Therefore, it is urgent to develop a new type of high-toughness shotcrete material that emits light under the deformation stress of the tunnel, and dynamically detects the stress and strain of the tunnel in real time and promotes its application. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. The present application provides a shotcrete material based on perovskite stress luminescence, a preparation method and its application, wherein the shotcrete material includes perovskite nanocrystals, which can provide early warning of coal mine roadway deformation, emit light under the action of coal mine roadway deformation stress, and during the application process, collect the intensity and distribution of the light signal emitted by the roadway stress in real time and dynamically through a visual camera, so as to reflect the ground stress and deformation of the coal mine roadway in real time and dynamically.

[0004] To achieve the above-mentioned purpose, according to the first aspect of the present application, a method for preparing a perovskite stress luminescent spraying material is proposed, comprising the following steps:

[0005] The method comprises adding a poor solvent to a good solvent of a perovskite precursor, adjusting the pH of the mixed solution after ultrasonic treatment, stirring, filtering and drying the mixed solution to prepare perovskite nanocrystals with stress luminescence effect; wherein the addition ratio of the good solvent to the poor solvent is 3:1;

[0006] By weight, 15-25 parts of the perovskite nanocrystals, 5-15 parts of nano-reinforced particles, 3-8 parts of nano-toughened fibers and 3.5 parts of additives are added to 100 parts of the gelling material, and the dry powder is stirred to obtain the spraying material.

[0007] In some embodiments, the preparation process of the good solvent is as follows: in terms of mass fractions, 20 parts of lead chloride are added to 100 parts of a mixed solvent prepared by mixing 2-methoxyethanol, tetrahydrofuran and acetonitrile in a mass ratio of 1:2:1, and the mixture is mixed and then subjected to solvent thermal treatment.

[0008] In some embodiments, the solvent thermal treatment parameters are heating in a water bath at 85-90° C. for 10-15 min.

[0009] In some embodiments, the poor solvent includes methyl benzoate, n-hexane, dimethyl sulfoxide, and dimethylformamide in a mass ratio of 3:1:4:1.

[0010] In some embodiments, the ultrasonic treatment parameters are a frequency of 90-100 kHz, a time of 50-60 minutes, and a power density of 7-10 W / cm 2 .

[0011] In some embodiments, during the pH adjustment process, the adjusting agent is a mixture of sodium hydroxide, potassium hydroxide, and sodium bicarbonate in a mass ratio of 1:1:5.

[0012] In some embodiments, the nano-reinforcement particles include carboxyl silver nanoparticles and vanadium oxide nanoparticles in a mass ratio of 1:2.

[0013] In some embodiments, the nano toughened fibers include nano zinc oxide fibers, nano tin oxide fibers, α-alumina fibers, and nano indium oxide fibers in a mass ratio of 2:1:1:1.

[0014] In some embodiments, the auxiliary agent includes 2 parts of accelerating setting agent, 1 part of water retaining agent and 0.5 parts of expansion agent in terms of weight.

[0015] In some embodiments, the cementitious material is sulphoaluminate clinker.

[0016] According to another purpose of the present application, a spraying material based on perovskite stress luminescence is proposed, which includes, by mass, 15-25 parts of perovskite nanocrystals, 5-15 parts of nano-reinforced particles, 3-8 parts of nano-toughened fibers, 3.5 parts of additives and 100 parts of cementitious material; the cementitious material is sulphoaluminate clinker.

[0017] In some embodiments, the auxiliary agent includes 2 parts of accelerating setting agent, 1 part of water retaining agent and 0.5 parts of expansion agent in terms of weight.

[0018] In some embodiments, the perovskite nanocrystals are prepared by adding a poor solvent to a good solvent of a perovskite precursor, adjusting the pH of the mixture after ultrasonic treatment, and stirring, filtering, and drying the mixture.

[0019] According to another object of the present application, it is proposed that the shotcrete material described in any of the above embodiments is used in coal mine tunnel deformation warning, and the shotcrete material described in any of the above embodiments emits light when sensing the stress and deformation of the coal mine tunnel.

[0020] Compared with the prior art, this application has the following advantages:

[0021] In the present application, perovskite nanocrystals, nano-reinforced particles, and nano-toughened fibers are added to the gelling material to prepare a new type of spraying material, wherein the perovskite nanocrystals generate a piezoelectric potential when stimulated by force due to their non-centrosymmetric crystal structure, thereby tilting the valence band and the conduction band, reducing the trap depth, and making it easier for electrons to be unbound. The unbound electrons and holes undergo non-radiative transition recombination, and the energy of the non-radiative transition is transferred to the lead atoms, causing them to be excited, and then emitting yellow light, which can be collected by an optical camera. At the same time, due to their nanometer size, the perovskite nanocrystals have a high specific surface area and high dispersibility, acting as stress concentration points, increasing the system interface area and interface energy, and can absorb deformation and impact energy, thereby enhancing the toughness of the spraying material.

[0022] In addition, in the hydration process of the shotcrete cementitious material, the perovskite nanocrystals, nano-reinforced particles, and nano-toughened fibers in this application act as nano-nucleation sites, thereby improving the hydration and crystallization of the cementitious material and increasing the mechanical strength of the shotcrete material. At the same time, it can provide early warning of coal mine roadway deformation, emit light under the action of coal mine roadway deformation stress, and collect the intensity and distribution of the light signal emitted by the roadway stress in real time and dynamically through the visual camera, reflecting the ground stress and deformation of the coal mine roadway in real time and dynamically.

[0023] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0025] Figure 1 This is a flow chart of a method for preparing a perovskite stress luminescent spray material in one embodiment of the present application.

[0026] Figure 2 yes Figure 1 Detailed flow chart. DETAILED DESCRIPTION

[0027] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be construed as limiting the present application. On the contrary, the embodiments of the present application include all changes, modifications and equivalents that fall within the spirit and connotation of the appended claims.

[0028] like Figure 1 As shown, in order to achieve the above-mentioned purpose, according to the first aspect of the present application, a preparation method based on perovskite stress luminescent spraying material is proposed, comprising the following steps:

[0029] S1: adding a poor solvent to a good solvent of a perovskite precursor, adjusting the pH of the mixture after ultrasonic treatment, stirring, filtering and drying the mixture to prepare perovskite nanocrystals with stress luminescence effect; wherein the addition ratio of the good solvent to the poor solvent is 3:1;

[0030] S2: By mass, add 15-25 parts of perovskite nanocrystals, 5-15 parts of nano-reinforced particles, 3-8 parts of nano-toughened fibers and 3.5 parts of additives to 100 parts of gelling material, and stir the dry powder to obtain the spraying material.

[0031] In S1, 20 parts of lead chloride are weighed according to the mass fractions, and added to 100 parts of a mixed solvent of 2-methoxyethanol, tetrahydrofuran and acetonitrile, wherein the mass ratio of 2-methoxyethanol, tetrahydrofuran and acetonitrile is 1:2:1; the mixture is stirred at 20°C for 30 minutes to obtain a good lead chloride solution, and the obtained solution is heated in a water bath at 85-90°C for 10-15 minutes to obtain a good solvent for the perovskite precursor.

[0032] like Figure 2 As shown, 40 parts of a poor solvent formed by a mixture of methyl benzoate, n-hexane, dimethyl sulfoxide, and dimethylformamide are weighed according to the mass fraction, wherein the mass ratio of methyl benzoate, n-hexane, dimethyl sulfoxide, and dimethylformamide is 3:1:4:1; 40 parts of the poor solvent are added to the good solvent of the above perovskite precursor, and the mixture is heated at a frequency of 90-100kHz and 7-10W / cm 2 The power density is set, and the ultrasound is stopped after 50-60 minutes. The mixed solution is adjusted with a pH regulator composed of sodium hydroxide, potassium hydroxide, and sodium bicarbonate, wherein the sodium hydroxide, potassium hydroxide, and sodium bicarbonate are mixed in a mass ratio of 1:1:5. When the pH of the mixed solution reaches the set value, it is stirred, filtered, and dried to obtain perovskite nanocrystals.

[0033] This embodiment adds a poor solvent to the good solvent of the perovskite precursor, assists with ultrasonic treatment, solvent heat treatment, and pH adjustment of the mixed solution, and finally prepares perovskite nanocrystals with stress luminescence effect. The perovskite nanocrystals in this application generate piezoelectric potential when stimulated by force due to their non-centrosymmetric crystal structure, which in turn tilts the valence band and conduction band, reduces the trap depth, and makes it easier for electrons to be unbound. The unbound electrons and holes undergo non-radiative transition recombination, and the energy of the non-radiative transition is transferred to the lead atoms, which are excited and then emit yellow light, which can be collected by the optical camera. At the same time, due to their nanometer size, the perovskite nanocrystals have a high specific surface area and high dispersibility, act as stress concentration points, increase the system interface area and interface energy, can absorb deformation and impact energy, and enhance the toughness of the spraying material.

[0034] like Figure 2 As shown, in S2, 15-25 parts of perovskite nanocrystals, 5-15 parts of nano-reinforced particles, 3-8 parts of nano-toughened fibers and 3.5 parts of additives are weighed by mass and added to 100 parts of the cementitious material, and mixed in a dry powder mixer for 15 minutes to obtain a spraying material; wherein the nano-reinforced particles include carboxyl silver nanoparticles and vanadium oxide nanoparticles in a mass ratio of 1:2; the nano-toughened fibers include nano zinc oxide fibers, nano tin oxide fibers, α-alumina fibers and nano indium oxide fibers in a mass ratio of 2:1:1:1; 2 parts of accelerator, 1 part of water retainer and 0.5 parts of expansion agent; the accelerator includes lithium sulfate, lithium carbonate and lithium chloride in a mass ratio of 1:1:3; the water retainer includes sodium carboxymethyl starch and sodium carboxymethyl cellulose in a mass ratio of 1:1; the expansion agent includes calcium oxide and magnesium oxide in a mass ratio of 1:2. In this embodiment, the cementitious material is sulphoaluminate clinker.

[0035] This application adds the prepared perovskite nanocrystals, nano-reinforced particles, and nano-toughened fibers to the cementitious material, and prepares a new type of shotcrete material in a scientific and reasonable proportion. The perovskite nanocrystals act as nano-nucleation sites, improve the hydration and crystallization of the cementitious material, and increase the mechanical strength of the shotcrete material. At the same time, it can provide early warning of coal mine roadway deformation, emit light under the action of coal mine roadway deformation stress, and collect the intensity and distribution of the light signal emitted by the roadway stress in real time and dynamically through the visual camera, reflecting the ground stress and deformation of the coal mine roadway in real time and dynamically.

[0036] The embodiments of the present application are based on 15-25 parts of perovskite nanocrystals, 5-15 parts of nano-reinforced particles, 3-8 parts of nano-toughened fibers, 2 parts of accelerator, 1 part of water-retaining agent and 0.5 parts of expansion agent, 100 parts of cementitious material and other components. The ratio is within the above range, which can improve the mechanical properties and bonding strength of the shotcrete material, so that it can be used for perovskite stress luminescence shotcrete material and its preparation method for early warning of coal mine tunnel deformation. At the same time, within the above range defined in the present application, the higher the frequency and power of ultrasound, the smaller the size of the perovskite nanocrystal; the lower the frequency and power of ultrasound, the larger the size of the perovskite nanocrystal; within the above range defined in the present application, the smaller the size of the perovskite nanocrystal or the more the amount used, the higher the luminescence intensity per unit area; the larger the size of the perovskite nanocrystal or the less the amount used, the lower the luminescence intensity per unit area; the more nano-reinforced particles, the higher the compressive strength of the grouting material; the fewer nano-reinforced particles, the lower the compressive strength of the grouting material; the more nano-toughened fibers, the higher the flexural strength of the grouting material; the fewer nano-toughened fibers, the lower the flexural strength of the grouting material;

[0037] In the embodiment of the present application, if the proportion of each component of the spraying material based on perovskite stress luminescence for coal mine tunnel deformation warning exceeds the above range, it will have a negative impact on the improvement of the unit area luminescence intensity, mechanical properties, etc. of the spraying material. For example, if the size of the perovskite nanocrystal is too large, the unit area luminescence intensity is too low; if the size of the perovskite nanocrystal is too small, the perovskite nanocrystal is easy to agglomerate, and the unit area luminescence intensity is reduced; if the amount of perovskite nanocrystal is too large, the compressive strength of the spraying material is reduced; if the amount of perovskite nanocrystal is too small, the unit area luminescence intensity is reduced; if the content of nano-reinforced particles is too low, the strength improvement effect of the spraying material is not good; if the content of nano-reinforced particles is too high, the dispersion of nano-reinforced particles in the matrix is ​​affected, and the strength improvement effect of the spraying material is not good; if the content of carbon quantum dots is too high, the strength of the grouting material is reduced; if the content of nano-toughened fibers is too high, the dispersion in the matrix is ​​uneven, and the toughness improvement effect of the spraying material is not good; if the content of nano-toughened fibers is too low, the toughness improvement effect of the spraying material is not large;.

[0038] Therefore, the shotcrete material of the present application is simple, low-cost, has outstanding mechanical property improvement effect, can sense tunnel stress and deformation and emit light, and is suitable for coal mine tunnel deformation warning, and is a perovskite stress-luminescent shotcrete material and its preparation method.

[0039] According to another purpose of the present application, a spraying material based on perovskite stress luminescence is proposed, which includes, by mass, 15-25 parts of perovskite nanocrystals, 5-15 parts of nano-reinforced particles, 3-8 parts of nano-toughened fibers, 3.5 parts of additives and 100 parts of cementitious material; the cementitious material is sulfoaluminate clinker.

[0040] Among them, this embodiment proposes a spraying material based on perovskite stress luminescence, which includes 15 parts of perovskite nanocrystals, 5 parts of nano-reinforced particles, 3 parts of nano-toughened fibers, 3.5 parts of additives and 100 parts of cementitious materials by weight; the cementitious material is sulfoaluminate clinker; the perovskite nanocrystals are prepared by adding a poor solvent to a good solvent of a perovskite precursor, adjusting the pH of the mixed solution after ultrasonic treatment, stirring, filtering and drying the mixed solution, and the specific steps are obtained by referring to the method in the above embodiment and will not be repeated. In addition, according to the weight, the additives include 2 parts of accelerator, 1 part of water retainer and 0.5 parts of expansion agent, wherein the selection of accelerator, water retainer and expansion agent is referred to the above embodiment and will not be repeated.

[0041] According to another object of the present application, it is proposed that the shotcrete material in any of the above embodiments is used in coal mine tunnel deformation early warning, and the shotcrete material in any of the above embodiments emits light when sensing the stress and deformation of the coal mine tunnel.

[0042] The following is a specific example of the preparation method of the perovskite stress luminescent spray material.

[0043] Example 1

[0044] Preparation of perovskite nanocrystals: Weigh 20 kg of lead chloride, add it to a mixture of 25 kg of 2-methoxyethanol, 50 kg of tetrahydrofuran and 25 kg of acetonitrile, stir at 20°C for 30 minutes to mix evenly to obtain a good lead chloride solution, and heat the obtained solution in a 90°C water bath for 10 minutes to obtain a good solvent for the perovskite precursor.

[0045] Methyl benzoate, n-hexane, dimethyl sulfoxide and dimethylformamide were mixed in a mass ratio of 3:1:4:1 to obtain 40 kg of a poor solvent; 40 kg of the poor solvent was added to the good solvent of the perovskite precursor at a frequency of 90 kHz and 7 W / cm 2 The power density was set at 1000 W and the ultrasonic treatment was carried out for 60 minutes. The ultrasonic treatment was stopped and a pH regulator prepared by mixing sodium hydroxide, potassium hydroxide and sodium bicarbonate in a mass ratio of 1:1:5 was added to the solution. The solution was stirred, filtered and dried to obtain perovskite nanocrystals. The amount of the pH regulator was small and its weight was not calculated during the measurement process.

[0046] Prepare 3.5 kg of auxiliary agent by mixing 2 kg of accelerating setting agent, 1 kg of water retaining agent and 0.5 kg of expansion agent;

[0047] 8 kg of nano-enhanced particles are prepared by mixing carboxyl silver nanoparticles and vanadium oxide nanoparticles in a mass ratio of 1:2;

[0048] To prepare 5 kg of nano toughened fibers, 2 kg of nano zinc oxide fibers, 1 kg of nano tin oxide fibers, 1 kg of α-alumina fibers, and 1 kg of nano indium oxide fibers are mixed.

[0049] Weigh 20 kg of perovskite nanocrystals, 8 kg of nano-reinforced particles, 5 kg of nano-toughened fibers, and 3.5 kg of additives and add them to 100 kg of sulphoaluminate clinker. Mix them in a dry powder mixer for 15 minutes to obtain 136.5 kg of stress luminescent spraying material. The product quality indicators are as follows:

[0050] Perovskite nanocrystal size: 114nm;

[0051] Stress luminescence intensity per unit area: 321Lux;

[0052] Flexural strength of shotcrete material: 13.2MPa.

[0053] Compressive strength of shotcrete material: 61MPa.

[0054] Example 2

[0055] Preparation of perovskite nanocrystals: Weigh 20 kg of lead chloride, add it to a mixture of 25 kg of 2-methoxyethanol, 50 kg of tetrahydrofuran and 25 kg of acetonitrile, stir at 20°C for 30 minutes to mix evenly to obtain a good lead chloride solution, and heat the obtained solution in a 90°C water bath for 10 minutes to obtain a good solvent for the perovskite precursor.

[0056] Methyl benzoate, n-hexane, dimethyl sulfoxide and dimethylformamide were mixed in a mass ratio of 3:1:4:1 to obtain 40 kg of a poor solvent; 40 kg of the poor solvent was added to the good solvent of the perovskite precursor at a frequency of 100 kHz and 10 W / cm 2 The power density was set at 1000 W and the ultrasonic treatment was carried out for 60 minutes. The ultrasonic treatment was stopped and a pH regulator prepared by mixing sodium hydroxide, potassium hydroxide and sodium bicarbonate in a mass ratio of 1:1:5 was added to the solution. The solution was stirred, filtered and dried to obtain perovskite nanocrystals. The amount of the pH regulator was small and its weight was not calculated during the measurement process.

[0057] Prepare 3.5 kg of auxiliary agent by mixing 2 kg of accelerating setting agent, 1 kg of water retaining agent and 0.5 kg of expansion agent;

[0058] 8 kg of nano-enhanced particles are prepared by mixing carboxyl silver nanoparticles and vanadium oxide nanoparticles in a mass ratio of 1:2;

[0059] To prepare 5 kg of nano toughened fibers, 2 kg of nano zinc oxide fibers, 1 kg of nano tin oxide fibers, 1 kg of α-alumina fibers, and 1 kg of nano indium oxide fibers are mixed.

[0060] Weigh 20 kg of perovskite nanocrystals, 8 kg of nano-reinforced particles, 5 kg of nano-toughened fibers, and 3.5 kg of additives and add them to 100 kg of sulphoaluminate clinker. Mix them in a dry powder mixer for 15 minutes to obtain 136.5 kg of stress luminescent spraying material. The product quality indicators are as follows:

[0061] Perovskite nanocrystal size: 82nm;

[0062] Stress luminescence intensity per unit area: 341Lux;

[0063] Flexural strength of shotcrete material: 13.5MPa.

[0064] Compressive strength of shotcrete material: 63MPa.

[0065] Example 3

[0066] Preparation of perovskite nanocrystals: Weigh 20 kg of lead chloride, add it to a mixture of 25 kg of 2-methoxyethanol, 50 kg of tetrahydrofuran and 25 kg of acetonitrile, stir at 20°C for 30 minutes to mix evenly to obtain a good lead chloride solution, and heat the obtained solution in a 90°C water bath for 10 minutes to obtain a good solvent for the perovskite precursor.

[0067] Methyl benzoate, n-hexane, dimethyl sulfoxide and dimethylformamide were mixed in a mass ratio of 3:1:4:1 to obtain 40 kg of a poor solvent; 40 kg of the poor solvent was added to the good solvent of the perovskite precursor at a frequency of 90 kHz and 7 W / cm 2 The power density was set at 1000 W and the ultrasonic treatment was carried out for 60 minutes. The ultrasonic treatment was stopped and a pH regulator prepared by mixing sodium hydroxide, potassium hydroxide and sodium bicarbonate in a mass ratio of 1:1:5 was added to the solution. The solution was stirred, filtered and dried to obtain perovskite nanocrystals. The amount of the pH regulator was small and its weight was not calculated during the measurement process.

[0068] 8 kg of nano-enhanced particles are prepared by mixing carboxyl silver nanoparticles and vanadium oxide nanoparticles in a mass ratio of 1:2;

[0069] To prepare 5 kg of nano toughened fibers, 2 kg of nano zinc oxide fibers, 1 kg of nano tin oxide fibers, 1 kg of α-alumina fibers, and 1 kg of nano indium oxide fibers are mixed.

[0070] Weigh 25 kg of perovskite nanocrystals, 8 kg of nano-reinforced particles, 5 kg of nano-toughened fibers, and 3.5 kg of additives and add them to 100 kg of sulphoaluminate clinker. Mix them in a dry powder mixer for 15 minutes to obtain 141.5 kg of stress luminescent spraying material. The product quality indicators are as follows:

[0071] Perovskite nanocrystal size: 114nm;

[0072] Stress luminous intensity per unit area: 366Lux;

[0073] Flexural strength of shotcrete material: 15.9MPa.

[0074] Compressive strength of shotcrete material: 78MPa.

[0075] Example 4

[0076] Preparation of perovskite nanocrystals: Weigh 20 kg of lead chloride, add it to a mixture of 25 kg of 2-methoxyethanol, 50 kg of tetrahydrofuran and 25 kg of acetonitrile, stir at 20°C for 30 minutes to mix evenly to obtain a good lead chloride solution, and heat the obtained solution in a 90°C water bath for 10 minutes to obtain a good solvent for the perovskite precursor.

[0077] Methyl benzoate, n-hexane, dimethyl sulfoxide and dimethylformamide were mixed in a mass ratio of 3:1:4:1 to obtain 40 kg of a poor solvent; 40 kg of the poor solvent was added to the good solvent of the perovskite precursor at a frequency of 90 kHz and 7 W / cm 2 The power density was set at 1000 W and the ultrasonic treatment was carried out for 60 minutes. The ultrasonic treatment was stopped and a pH regulator prepared by mixing sodium hydroxide, potassium hydroxide and sodium bicarbonate in a mass ratio of 1:1:5 was added to the solution. The solution was stirred, filtered and dried to obtain perovskite nanocrystals. The amount of the pH regulator was small and its weight was not calculated during the measurement process.

[0078] Prepare 3.5 kg of auxiliary agent by mixing 2 kg of accelerating setting agent, 1 kg of water retaining agent and 0.5 kg of expansion agent;

[0079] 8 kg of nano-enhanced particles are prepared by mixing carboxyl silver nanoparticles and vanadium oxide nanoparticles in a mass ratio of 1:2;

[0080] To prepare 5 kg of nano toughened fibers, 2 kg of nano zinc oxide fibers, 1 kg of nano tin oxide fibers, 1 kg of α-alumina fibers, and 1 kg of nano indium oxide fibers are mixed.

[0081] Weigh 15 kg of perovskite nanocrystals, 8 kg of nano-reinforced particles, 5 kg of nano-toughened fibers, and 3.5 kg of additives and add them to 100 kg of sulphoaluminate clinker. Mix them in a dry powder mixer for 15 minutes to obtain 131.5 kg of stress luminescent spraying material. The product quality indicators are as follows:

[0082] Perovskite nanocrystal size: 114nm;

[0083] Stress luminous intensity per unit area: 319Lux;

[0084] Flexural strength of shotcrete material: 13.3MPa.

[0085] Compressive strength of shotcrete material: 60MPa.

[0086] Example 5

[0087] Preparation of perovskite nanocrystals: Weigh 20 kg of lead chloride, add it to a mixture of 25 kg of 2-methoxyethanol, 50 kg of tetrahydrofuran and 25 kg of acetonitrile, stir at 20°C for 30 minutes to mix evenly to obtain a good lead chloride solution, and heat the obtained solution in a 90°C water bath for 10 minutes to obtain a good solvent for the perovskite precursor.

[0088] Methyl benzoate, n-hexane, dimethyl sulfoxide and dimethylformamide were mixed in a mass ratio of 3:1:4:1 to obtain 40 kg of a poor solvent; 40 kg of the poor solvent was added to the good solvent of the perovskite precursor at a frequency of 90 kHz and 7 W / cm 2 The power density was set at 1000 W and the ultrasonic treatment was carried out for 60 minutes. The ultrasonic treatment was stopped and a pH regulator prepared by mixing sodium hydroxide, potassium hydroxide and sodium bicarbonate in a mass ratio of 1:1:5 was added to the solution. The solution was stirred, filtered and dried to obtain perovskite nanocrystals. The amount of the pH regulator was small and its weight was not calculated during the measurement process.

[0089] Prepare 3.5 kg of auxiliary agent by mixing 2 kg of accelerating setting agent, 1 kg of water retaining agent and 0.5 kg of expansion agent;

[0090] 15 kg of nano-enhanced particles are prepared by mixing 5 kg of carboxyl silver nanoparticles and 10 kg of vanadium oxide nanoparticles;

[0091] To prepare 5 kg of nano toughened fibers, 2 kg of nano zinc oxide fibers, 1 kg of nano tin oxide fibers, 1 kg of α-alumina fibers, and 1 kg of nano indium oxide fibers are mixed.

[0092] Weigh 20 kg of perovskite nanocrystals, 15 kg of nano-reinforced particles, 5 kg of nano-toughened fibers, and 3.5 kg of additives and add them to 100 kg of sulphoaluminate clinker. Mix them in a dry powder mixer for 15 minutes to obtain 143.5 kg of stress luminescent spraying material. The product quality indicators are as follows:

[0093] Perovskite nanocrystal size: 114nm;

[0094] Stress luminous intensity per unit area: 322Lux;

[0095] Flexural strength of shotcrete material: 13.3MPa.

[0096] Compressive strength of shotcrete material: 83MPa.

[0097] Example 6

[0098] Preparation of perovskite nanocrystals: Weigh 20 kg of lead chloride, add it to a mixture of 25 kg of 2-methoxyethanol, 50 kg of tetrahydrofuran and 25 kg of acetonitrile, stir at 20°C for 30 minutes to mix evenly to obtain a good lead chloride solution, and heat the obtained solution in a 90°C water bath for 10 minutes to obtain a good solvent for the perovskite precursor.

[0099] Methyl benzoate, n-hexane, dimethyl sulfoxide and dimethylformamide were mixed in a mass ratio of 3:1:4:1 to obtain 40 kg of a poor solvent; 40 kg of the poor solvent was added to the good solvent of the perovskite precursor at a frequency of 90 kHz and 7 W / cm 2 The power density was set at 1000 W and the ultrasonic treatment was carried out for 60 minutes. The ultrasonic treatment was stopped and a pH regulator prepared by mixing sodium hydroxide, potassium hydroxide and sodium bicarbonate in a mass ratio of 1:1:5 was added to the solution. The solution was stirred, filtered and dried to obtain perovskite nanocrystals. The amount of the pH regulator was small and its weight was not calculated during the measurement process.

[0100] Prepare 3.5 kg of auxiliary agent by mixing 2 kg of accelerating setting agent, 1 kg of water retaining agent and 0.5 kg of expansion agent;

[0101] 5 kg of nano-enhanced particles are prepared by mixing carboxyl silver nanoparticles and vanadium oxide nanoparticles in a mass ratio of 1:2;

[0102] To prepare 5 kg of nano toughened fibers, 2 kg of nano zinc oxide fibers, 1 kg of nano tin oxide fibers, 1 kg of α-alumina fibers, and 1 kg of nano indium oxide fibers are mixed.

[0103] Weigh 20 kg of perovskite nanocrystals, 5 kg of nano-reinforced particles, 5 kg of nano-toughened fibers, and 3.5 kg of additives and add them to 100 kg of sulphoaluminate clinker. Mix them in a dry powder mixer for 15 minutes to obtain 133.5 kg of stress luminescent spraying material. The product quality indicators are as follows:

[0104] Perovskite nanocrystal size: 114nm;

[0105] Stress luminous intensity per unit area: 320Lux;

[0106] Flexural strength of shotcrete material: 13.0MPa.

[0107] Compressive strength of shotcrete material: 53MPa.

[0108] Example 7

[0109] Preparation of perovskite nanocrystals: Weigh 20 kg of lead chloride, add it to a mixture of 25 kg of 2-methoxyethanol, 50 kg of tetrahydrofuran and 25 kg of acetonitrile, stir at 20°C for 30 minutes to mix evenly to obtain a good lead chloride solution, and heat the obtained solution in a 90°C water bath for 10 minutes to obtain a good solvent for the perovskite precursor.

[0110] Methyl benzoate, n-hexane, dimethyl sulfoxide and dimethylformamide were mixed in a mass ratio of 3:1:4:1 to obtain 40 kg of a poor solvent; 40 kg of the poor solvent was added to the good solvent of the perovskite precursor at a frequency of 90 kHz and 7 W / cm 2 The power density was set at 1000 W and the ultrasonic treatment was carried out for 60 minutes. The ultrasonic treatment was stopped and a pH regulator prepared by mixing sodium hydroxide, potassium hydroxide and sodium bicarbonate in a mass ratio of 1:1:5 was added to the solution. The solution was stirred, filtered and dried to obtain perovskite nanocrystals. The amount of the pH regulator was small and its weight was not calculated during the measurement process.

[0111] Prepare 3.5 kg of auxiliary agent by mixing 2 kg of accelerating setting agent, 1 kg of water retaining agent and 0.5 kg of expansion agent;

[0112] 8 kg of nano-enhanced particles are prepared by mixing carboxyl silver nanoparticles and vanadium oxide nanoparticles in a mass ratio of 1:2;

[0113] To prepare 8 kg of nano toughened fibers, 3.2 kg of nano zinc oxide fibers, 1.6 kg of nano tin oxide fibers, 1.6 kg of α-alumina fibers, and 1.6 kg of nano indium oxide fibers are mixed.

[0114] Weigh 20 kg of perovskite nanocrystals, 8 kg of nano-reinforced particles, 8 kg of nano-toughened fibers, and 3.5 kg of additives and add them to 100 kg of sulphoaluminate clinker. Mix them in a dry powder mixer for 15 minutes to obtain 139.5 kg of stress luminescent spraying material. The product quality indicators are as follows:

[0115] Perovskite nanocrystal size: 114nm;

[0116] Stress luminous intensity per unit area: 324Lux;

[0117] Flexural strength of shotcrete material: 16.2MPa.

[0118] Compressive strength of shotcrete material: 63MPa.

[0119] Example 8

[0120] Preparation of perovskite nanocrystals: Weigh 20 kg of lead chloride, add it to a mixture of 25 kg of 2-methoxyethanol, 50 kg of tetrahydrofuran and 25 kg of acetonitrile, stir at 20°C for 30 minutes to mix evenly to obtain a good lead chloride solution, and heat the obtained solution in a 90°C water bath for 10 minutes to obtain a good solvent for the perovskite precursor.

[0121] Methyl benzoate, n-hexane, dimethyl sulfoxide and dimethylformamide were mixed in a mass ratio of 3:1:4:1 to obtain 40 kg of a poor solvent; 40 kg of the poor solvent was added to the good solvent of the perovskite precursor at a frequency of 90 kHz and 7 W / cm 2 The power density was set at 1000 W and the ultrasonic treatment was carried out for 60 minutes. The ultrasonic treatment was stopped and a pH regulator prepared by mixing sodium hydroxide, potassium hydroxide and sodium bicarbonate in a mass ratio of 1:1:5 was added to the solution. The solution was stirred, filtered and dried to obtain perovskite nanocrystals. The amount of the pH regulator was small and its weight was not calculated during the measurement process.

[0122] Prepare 3.5 kg of auxiliary agent by mixing 2 kg of accelerating setting agent, 1 kg of water retaining agent and 0.5 kg of expansion agent;

[0123] 8 kg of nano-enhanced particles are prepared by mixing carboxyl silver nanoparticles and vanadium oxide nanoparticles in a mass ratio of 1:2;

[0124] To prepare 3 kg of nano toughened fibers, 1.2 kg of nano zinc oxide fibers, 0.6 kg of nano tin oxide fibers, 0.6 kg of α-alumina fibers, and 0.6 kg of nano indium oxide fibers are mixed.

[0125] Weigh 20 kg of perovskite nanocrystals, 8 kg of nano-reinforced particles, 3 kg of nano-toughened fibers, and 3.5 kg of additives and add them to 100 kg of sulphoaluminate clinker. Mix them in a dry powder mixer for 15 minutes to obtain 134.5 kg of stress luminescent spraying material. The product quality indicators are as follows:

[0126] Perovskite nanocrystal size: 114nm;

[0127] Stress luminescence intensity per unit area: 321Lux;

[0128] Flexural strength of shotcrete material: 13.2MPa.

[0129] Compressive strength of shotcrete material: 61MPa.

[0130] Comparative Example 1

[0131] This comparative example refers to Example 1 in the process of preparing perovskite nanocrystals.

[0132] Prepare 3.5 kg of auxiliary agent by mixing 2 kg of accelerating setting agent, 1 kg of water retaining agent and 0.5 kg of expansion agent;

[0133] 6 kg of nano-enhanced particles are prepared by mixing 2 kg of carboxyl silver nanoparticles and 4 kg of vanadium oxide nanoparticles;

[0134] To prepare 3 kg of nano toughened fibers, 1.2 kg of nano zinc oxide fibers, 0.6 kg of nano tin oxide fibers, 0.6 kg of α-alumina fibers, and 0.6 kg of nano indium oxide fibers are mixed.

[0135] 17 kg of perovskite nanocrystals, 14 kg of nano-reinforced particles, and 6 kg of nano-toughened fibers were weighed and added into 100 kg of sulphoaluminate clinker, and mixed in a dry powder mixer for 15 minutes to obtain a stress luminescent spraying material; and the product quality indicators were tested.

[0136] Perovskite nanocrystal size: 114nm;

[0137] Stress luminous intensity per unit area: 323Lux;

[0138] Flexural strength of shotcrete material: 11.4MPa.

[0139] Compressive strength of shotcrete material: 46MPa.

[0140] Comparative Example 2

[0141] Compared with Example 1, in the process of preparing perovskite nanocrystals, 20 kg of lead chloride was weighed and added to a mixture of 25 kg of 2-methoxyethanol, 50 kg of tetrahydrofuran and 25 kg of acetonitrile, and stirred at 20 ° C for 30 minutes to obtain a good lead chloride solution. The good lead chloride solution was added to the poor solvent at a frequency of 100 kHz and 7 W / cm 2 Power density, ultrasound for 60 minutes, and other technical features are referenced to Example 1.

[0142] Weigh 25 kg of perovskite nanocrystals, 5 kg of nano-reinforced particles, 5 kg of nano-toughened fibers, and 3.5 kg of additives and add them to 100 kg of sulphoaluminate clinker. Mix them in a dry powder mixer for 15 minutes to obtain stress luminescent spraying material. The product quality indicators are tested as follows.

[0143] Perovskite nanocrystal size: 214nm;

[0144] Stress luminescence intensity per unit area: 207Lux;

[0145] Flexural strength of shotcrete material: 11.5MPa.

[0146] Compressive strength of shotcrete material: 49MPa.

[0147] Comparative Example 3

[0148] Compared with Example 1, this comparative example mixes methyl benzoate, n-hexane, dimethyl sulfoxide and dimethylformamide in a mass ratio of 3:1:4:1 to obtain 40 kg of a poor solvent; 40 kg of the poor solvent is added to the above-mentioned good solvent of the perovskite precursor, and after mixing, a pH adjuster prepared by mixing sodium hydroxide, potassium hydroxide and sodium bicarbonate in a mass ratio of 1:1:5 is added to the solution, and the solution is stirred, filtered and dried to obtain a solid. Other technical features are referred to Example 1.

[0149] Weigh 25 kg of solid matter, 5 kg of nano-reinforced particles, 5 kg of nano-toughened fibers, and 3.5 kg of additives and add them to 100 kg of sulphoaluminate clinker. Mix them in a dry powder mixer for 15 minutes to obtain stress luminescent spraying material. The product quality indicators are tested as follows.

[0150] Perovskite nanocrystal size: 251nm;

[0151] Stress luminescence intensity per unit area: 183Lux;

[0152] Flexural strength of shotcrete material: 11.8MPa.

[0153] Compressive strength of shotcrete material: 48MPa.

[0154] Comparative Example 4

[0155] Compared with Example 1, this comparative example weighed 25 kg of ordinary nanocrystals, 5 kg of nano-reinforced particles, 5 kg of nano-toughened fibers, and 3.5 kg of additives, added into 100 kg of sulphoaluminate clinker, mixed in a dry powder mixer for 15 minutes to obtain a stress luminescent spraying material, and the product quality indicators were tested as follows.

[0156] Perovskite nanocrystal size: 321 microns;

[0157] Stress luminous intensity per unit area: 64Lux;

[0158] Flexural strength of shotcrete material: 10.3MPa.

[0159] Compressive strength of shotcrete material: 42MPa.

[0160] Comparative Example 5

[0161] Compared with Example 1, this comparative example weighed 10 kg of perovskite nanocrystals, 20 kg of nano-reinforced particles, 3 kg of nano-toughened fibers, and 3.5 kg of additives, added them into 100 kg of sulphoaluminate clinker, and mixed them in a dry powder mixer for 15 minutes to obtain a stress luminescent spraying material.

[0162] Perovskite nanocrystal size: 115nm;

[0163] Stress luminescence intensity per unit area: 367Lux;

[0164] Flexural strength of shotcrete material: 8.3MPa.

[0165] Compressive strength of shotcrete material: 32MPa.

[0166] Comparative Example 6

[0167] Compared with Example 1, 16 kg of perovskite nanocrystals, 14 kg of nano-enhanced particles, and 3.5 kg of additives were weighed into 100 kg of sulphoaluminate clinker, and mixed in a dry powder mixer for 15 minutes to obtain a stress luminescent spraying material.

[0168] Perovskite nanocrystal size: 114nm;

[0169] Stress luminous intensity per unit area: 325Lux;

[0170] Flexural strength of shotcrete material: 8.2MPa.

[0171] Compressive strength of shotcrete material: 57MPa.

[0172] Comparative Example 7

[0173] Compared with Example 1, this comparative example weighed 20 kg of perovskite nanocrystals, 8 kg of nano-toughened fibers, and 3.5 kg of additives, added them into 100 kg of sulphoaluminate clinker, and mixed them in a dry powder mixer for 15 minutes to obtain a stress luminescent spraying material.

[0174] Perovskite nanocrystal size: 114nm;

[0175] Stress luminous intensity per unit area: 323Lux;

[0176] Flexural strength of shotcrete material: 13.1MPa;

[0177] Compressive strength of shotcrete material: 40MPa.

[0178] It should be noted that, in the description of this application, the terms "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance. In addition, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0179] Any process or method description in a flowchart or otherwise described herein may be understood to represent a module, segment or portion of code that includes one or more executable instructions for implementing the steps of a specific logical function or process, and the scope of the preferred embodiments of the present application includes alternative implementations in which functions may not be performed in the order shown or discussed, including performing functions in a substantially simultaneous manner or in the reverse order depending on the functions involved, which should be understood by technicians in the technical field to which the embodiments of the present application belong.

[0180] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0181] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for preparing a perovskite stress luminescent spraying material, characterized in that: The steps include: A poor solvent is added to a good solvent of a perovskite precursor, and the pH of the mixed solution is adjusted after ultrasonic treatment, and the mixed solution is stirred, filtered, and dried to prepare a perovskite nanocrystal with a stress luminescence effect; wherein the mass ratio of the good solvent to the poor solvent is 3:1; the preparation process of the good solvent is: in terms of mass parts, 20 parts of lead chloride are added to 100 parts of a mixed solvent in which 2-methoxyethanol, tetrahydrofuran and acetonitrile are mixed in a mass ratio of 1:2:1, and the mixture is mixed and then subjected to solvent thermal treatment; the poor solvent includes methyl benzoate, n-hexane, dimethyl sulfoxide and dimethylformamide in a mass ratio of 3:1:4:1; In terms of mass, 15-25 parts of the perovskite nanocrystals, 5-15 parts of nano-reinforced particles, 3-8 parts of nano-toughened fibers and 3.5 parts of additives are added to 100 parts of cementitious material, and the dry powder is stirred to obtain the spraying material; the cementitious material is sulphoaluminate clinker.

2. The preparation method according to claim 1, characterized in that: The solvent thermal treatment parameters are heating in a water bath at 85-90°C for 10-15 min.

3. The preparation method according to claim 1 or 2, characterized in that: The ultrasonic treatment parameters are frequency 90-100kHz, time 50-60 minutes, and power density 7-10W / cm².

4. The preparation method according to claim 3, characterized in that: During the pH adjustment process, the adjusting agent is a mixture of sodium hydroxide, potassium hydroxide and sodium bicarbonate in a mass ratio of 1:1:

5.

5. The preparation method according to claim 3, characterized in that: The nano-enhanced particles include carboxyl silver nano-particles and vanadium oxide nano-particles in a mass ratio of 1:

2.

6. The preparation method according to claim 3, characterized in that: The nano toughening fiber comprises nano zinc oxide fiber, nano tin oxide fiber, alpha aluminum oxide fiber and nano indium oxide fiber in a mass ratio of 2:1:1:

1.

7. The preparation method according to claim 3, characterized in that: Calculated by weight, the additives include 2 parts of accelerating setting agent, 1 part of water retaining agent and 0.5 parts of expansion agent.

8. A spraying material based on perovskite stress luminescence, characterized in that: It is obtained by the preparation method described in any one of claims 1 to 7, wherein the shotcrete material comprises, by weight, 15-25 parts of perovskite nanocrystals, 5-15 parts of nano-reinforced particles, 3-8 parts of nano-toughened fibers, 3.5 parts of additives and 100 parts of a cementitious material; the cementitious material is sulphoaluminate clinker.

9. The application of the shotcrete material according to claim 8 in coal mine tunnel deformation early warning is characterized in that: The shotcrete material emits light when sensing stress and deformation in the coal mine tunnel.

Citation Information

Patent Citations

  • Method and device for monitoring roadway surrounding rock stress and deformation on lines

    CN110986812A

  • Flexible perovskite scintillator thick film and preparation method thereof

    CN113061313A